DAMPAK PERSEPSI NILAI TERHADAP KESETIAAN KONSUMEN TRANSPORTASI ONLINE - Yeri Resika (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
This research aims to determine the influence of perceive value on the loyalty of online transportation customers. The analytical techniques used are quantitative analysis using simple regression methods. The method used in this research is a simple regression analysis using the SPSS. The result of this research shows that the customer perceive value can be a positive influence on customer loyalty. Variable indicators of customer perceive value demonstrate strong values affecting customer loyalty such as inexpensive fares as well as fast ordering processes.